Fire and ash - Maberry, Jonathan (London : Simon & Schuster, 2013)
When Benny and his friends learn that a scientist may have discovered a cure for the zombie plague, they mount a search and rescue mission, unaware that the reapers want the cure to wipe humanity off the face of the earth.
Young Adult.
Young Adult
Keywords: Survival -- Juvenile fiction; Zombies -- Juvenile fiction; Horror stories; Survival -- Fiction; Zombies -- Fiction; Horror fiction; Survival skills -- Fiction; Zombies -- Fiction; Horror fiction